The Role of Collaborative Leadership in Enhancing Educational Management Systems in Primary Schools - Sudirman Sudirman; Abu Hasan Agus R (Universitas Nurul Jadid, 2025)
This study examines the impact of collaborative leadership in improving the quality of education in public elementary schools. The background of this research highlights the growing need for effective school leadership, especially in rural areas, to address challenges in educational quality. The study adopted a qualitative case study approach, utilizing desk reviews, observations, and semi-structured interviews with school leaders, teachers, parents, and students to collect data. The findings show that implementing collaborative leadership has led to a more effective decision-making process, fostering a sense of ownership and commitment to educational goals among all stakeholders. Effective communication within the school community was also identified as an important factor in improving leadership practices and ensuring alignment between teachers, parents, and students. Parental involvement in school decision-making and activities significantly contributes to student success, emphasizing the importance of collaboration outside of the classroom. The study further shows that this leadership model has fostered a more inclusive and supportive school culture, improving teaching effectiveness and student outcomes. This research offers implications for understanding collaborative leadership in Indonesian primary schools, a relatively underexplored context.